HIGHER EDUCATION QUALITY ASSURANCE: CURRENT PRACTICE IN GREAT BRITAIN - Avshenyuk, N.M. (Proceedings of National Aviation University (archive), 2005)
The article deals with an international problem of quality assurance in higher education. Despite the enormous growth in national quality assurance processes in Great Britain, serious doubts remain about their effectiveness in achieving lasting quality improvement. The paper suggests that the quality of students’ experience of higher education can more effectively be improved by combining educational development with quality assurance to create a more positive, not punitive approach. The concept of “quality development” is explained and mechanisms of this approach are described.